Optimization of ultrafiltration separation and quality analysis of the major royal jelly proteins - Li Meilu; Tan Liangliang; Qiu Wei; Yin Zhihong; Shen Lirong (浙江大学学报. 农业与生命科学版)
Royal jelly (RJ) is the exclusive food for the Western honeybee (Apis mellifera) queen throughout its lifespan and the primary food for the honeybee larvae during the first three days of life, which is secreted by hypopharyngeal and mandibular glands of nurse honey bees. The chemical composition of RJ is very complicate, while the protein components have been found to play critical roles in RJ. Around 50% of dry RJ is made up of proteins which could be divided into two parts, water-soluble proteins and water-insoluble proteins. The water-soluble proteins, accounting for 82% to 90% of the total RJ proteins, are named major royal jelly proteins (MRJPs) which belong to the same family composed of nine members. It has been proved that MRJPs have effects such as ant-i aging, immunoregulation and anti-fatigue, et al. In addition, MRJPs, especially MRJP1 are authenticated as the critical constituents to reveal the freshness of RJ and will be hopeful as one new functional component in future.In previous studies, various methods were developed for isolation of MRJPs, which included centrifugation, alkali extraction acid precipitation and column chromatography. However, a series of obstacles, such as low purity, solvent contamination and low productivity limited the application of those methods in honeybee industry. Ultrafiltration as a novel bio-separation technology has many advantages, such as simple operation, easy scale-up, and hence has a huge potentiality for large-scale isolation of bio-macromolecules. Our effort was to obtain the separation technology of MRJPs by using ultrafiltration and provide new knowledge for the industrial application of RJ process in future.Since the molecular masses of MRJPs are in the range of 4.9×104 8.7×104, the poly-sulfone hollow fiber membrane component used in the ultrafiltration equipment was comprised of two types with different molecular mass cut-off membranes. The ultrafiltration membrane with a 1×105 molecular mass cut-off was employed to remove macromolecular impurities, whereas the 4.9×104 cut-off membrane was employed to retain most of MRJPs. In this study, disposals were taken to separate soluble proteins, MRJPs from RJ by ultrafiltration. The control process included pH, ion intensity and ratio of water to material. In order to obtain the optimal conditions to extract MRJPs, orthogonal test was employed during investigation on experimental factors.The results showed that the optimal condition was as follows, ratio of water to material 5∶1, ion intensity 0.5 mol/L and pH 7.0. Under the optimal condition, 82.63% of MRJPs was extracted from fresh RJ. It was determined that the lyophilized powder of MRJPs contained 91.00% soluble protein, 0.01% moisture, 2.00% 10-HDA and 15.22% total sugar. Besides, the by-products contained 10-HDA and total sugar were recycled, and the recycling rate of the two components reached 3.60% and 2.11%, respectively.This method with many advantages, such as no solvent pollution and fully utilization of 10-HDA, has provided a new technology for MRJPs separation by first using ultrafiltration in deep process of RJ, and will be hopeful for large scale application in RJ process industry.